SPS 2000 demonstration of energy reception by microwave rectennas in Malaysia - Rosmin, Norzanah; Mohd. Taha, Faridah; Esa, Mazlina; Matsuoka,, H.; Collin, P. (IEEE, 2003)
As the worlds' population increases, the demand for energy, particularly electrical energy also increases. However, due to the depletion of energy in particular the hydrocarbons with time, an alternative sources is needed. Solar energy is one of the safest to be explored. This paper presents an approach in using solar power to generate electrical energy in the future using an SPS 2000 (solar power satellite) rectenna. The suitable location of the rectenna in Malaysia has been identified. Spherical rectenna is chosen for optimized reception area and for ease of analysis. The amount of energy received by this rectenna is simulated using Visual Basic V.5.0. The latitude of the rectenna, rectenna radius, earth inclination, distance between rectenna and satellite and the time of the year of inception determine energy reception. The program also estimates the price per kWh of energy generated. However, this is not the real of electricity as the satellite and the transmitting costs were not considered in the calculation.